Elevated Depressive Symptoms Among Hired Crop Workers in the United States: Variation by Sociodemographic and Employment Characteristics - Alterman, Toni (Rural Ment Health, 2018)
We present prevalence rates, along with demographic and economic characteristics associated with elevated depressive symptoms (EDS), in a nationally representative sample of hired crop workers in the United States. We analyzed in-person interviews with 3,691 crop workers collected in 2009–2010 as part of a mental health and psychosocial supplement to the National Agricultural Workers Survey. The prevalence of EDS was 8.3% in men and 17.1% in women. For men, multivariate analysis showed that EDS was associated with years of education, family composition, having a great deal of difficulty being separated from family, having fair or poor general health, ability to read English, fear of being fired from their current farm job, and method of payment (piece, salary, or a combination). Interactions were found between region of the country and family composition. Multivariate analyses for women showed that fear of being fired, fair or poor general health, having children ≤15 years of age, being unaccompanied by their nuclear family, expectation for length of time continuing to do farm work in the United States, and authorization status were associated with EDS. Interactions were found with Hispanic ethnicity and region of the country, as well as presence of the nuclear family and region. The present study identifies important risk factors in this first population-based assessment of EDS in a nationally representative sample of U.S. crop workers. The importance of social support from family, job insecurity, and high prevalence of EDS in female crop workers support the need for screening and outreach in this primarily rural group of men and women crop workers.